Postcolonial readings of suicide in George Orwell and Chinua Achebe - Martins, Adriana Alves de Paula (2007)
By transforming suicide into an ethical, semantic and politicai parameter, in this essay I reflect on the deficits of colonization through the comparative analysis of two novels Burmese Days by George Orwell and Things Fali Apart by Chinua Achebe. My aim is to examine how writers address forgotten histories and simultaneously discuss the history of a forgetting.